Making Research Works Visible and Stimulating a Research Milieu in the Field of Social Work – The European Resource Centre for Social Work Research (CERTS) - Geneviève Crespo (Social Work and Society, 2003)
The project to create a European Resource Centre for Social Work Research (CERTS) has been agreed in December 2001 by the General Research Board of the European Commission within the framework programme ‘Accompanying Measures for the improving the Human research potential and the Socio Economic Knowledge Base’.